Indigenizing philosophy through the land : a trickster methodology for decolonizing environmental ethics and Indigenous futures - Burkhart, Brian (American Indian studies series (East Lansing, Mich.), 2019)
"Indigenizing Philosophy through the Land articulates the way in which land acts as a material, conceptual, and ontological foundation for Indigenous ways of knowing, being, and valuing, and as the key to the operations of coloniality and decolonial liberation as well the framework for Indigenous environmental ethics, as a foundation of ethics rather than a derivative or applied field of ethics"--